2001
DOI: 10.2134/agronj2001.935967x
|View full text |Cite
|
Sign up to set email alerts
|

Competitiveness of Semidwarf Upland Rice Cultivars against Palisadegrass (Brachiaria brizantha) and Signalgrass (B. decumbens)

Abstract: Upland rice varieties tolerant to acid soil can be sown in the acid, well-drained savannah soils of Latin Amer-When savannas in Latin America are brought into cultivation, rice ica for the profitable production of grain while grazing (Oryza sativa L.) can be sown with the perennial grasses palisadegrass land is renovated (Cadavid and Smith, 1994; Friesen, [Brachiaria brizantha (Hochst. ex A. Rich) Stapf] and signalgrass (B. decumbens Stapf) to harvest a grain crop while establishing a 1994; Guimaraes, 1993). S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
69
1
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(83 citation statements)
references
References 18 publications
(33 reference statements)
7
69
1
6
Order By: Relevance
“…Silva & Durigan (2009), ao avaliarem por dois anos consecutivos as relações de interferência entre plantas daninhas e o arroz de terras altas, constataram que a convivência da comunidade infestante durante todo o ciclo da cultura promoveu significativa interferência, resultando em perdas de produtividade de grãos de aproximadamente 95%. Fischer et al (2001), em campo, verificaram que a competição por luz foi o fator crítico da interferência das braquiárias (B. brizantha e B. decumbens) sobre o arroz de terras altas, com perdas na produtividade de grãos variando de 18 a 55%. Com altas densidades de planta daninha, o dano à cultura ocorre logo após a emergência, ao passo que em densidades menores as injúrias começam a partir do início do perfilhamento (Tozani et al, 1995).…”
Section: Resultsunclassified
“…Silva & Durigan (2009), ao avaliarem por dois anos consecutivos as relações de interferência entre plantas daninhas e o arroz de terras altas, constataram que a convivência da comunidade infestante durante todo o ciclo da cultura promoveu significativa interferência, resultando em perdas de produtividade de grãos de aproximadamente 95%. Fischer et al (2001), em campo, verificaram que a competição por luz foi o fator crítico da interferência das braquiárias (B. brizantha e B. decumbens) sobre o arroz de terras altas, com perdas na produtividade de grãos variando de 18 a 55%. Com altas densidades de planta daninha, o dano à cultura ocorre logo após a emergência, ao passo que em densidades menores as injúrias começam a partir do início do perfilhamento (Tozani et al, 1995).…”
Section: Resultsunclassified
“…FISCHER et al (2001) verificaram mais competitividade do arroz associada com sua habilidade para interceptação da luz. FLECK et al (2003), na cultura do arroz irrigado, constataram que a velocidade de emergência e de crescimento inicial das plântulas de arroz foram características importantes na sua habilidade competitiva.…”
Section: Introductionunclassified
“…Souza et al (2006) reported allelopathic effects caused by the species Brachiaria, that can reduce crop seed germination, plant development and grain yield; similarly to what has occurred in this trial with Brachiaria ruziziensis and Brachiaria brizantha as cover crops. Fischer et al (1995Fischer et al ( , 2001, Nunes et al (2009) andCrusciol et al (2010) have added that Brachiaria spp. and Panicum spp.…”
Section: Resultsmentioning
confidence: 99%